Dinar-Bademli Mosque: Architectural Characteristics and Hand-Made Decorations on Plaster - Pakoz, Aslihan Ece; Bosdurmaz, Nurcan; Unal, Zeynep GUl (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
Bademli Mosque, in Bademli village of Afyonkarahisar, dates back to the late Ottoman period. In Afyonkarahisar, as in many other Anatolian cities, the influence of this period is visible in the adorning of mosques. Bademli Mosque is an important example as it has an extensive decoration program and preserves its original features. The mosque has timber posts and a flat roof, clad with timber. Its walls are adorned with colorful handmade decorations on plaster, the most noticeable one being Sultan Abdulhamid II's tughra in the last prayer hall. In addition, the calligraphy program that extends inward from the entrance of the mosque is remarkable in that it shows how the symbolic reflection of worship in the place was perceived at the beginning of the 20th century. The present study focuses on the mosque's rich handmade decorations, as well as its architectural characteristic. The study also provides suggestions for the preservation of the unique features of the Bademli Mosque, which have been poorly protected due to user-related problems and a lack of maintenance and repair. In this context, preservation project proposed by the authors in 2018 was used as a reference.
Keywords: Bademli Mosque; Dinar; handmade decoration; architectural characteristic; tughra; Architecture